Pengaruh Tingkat Pengangguran Terbuka Dan Inflasi Terhadap Pertumbuhan Ekonomi Di Provinsi Riau - Jhoni Frangki Manurung; Darwin Damanik (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the effect of inflation and the level and level of open unemployment on economic growth in Riau Province. The data used in this study include inflation, open unemployment rate, and economic growth from 2007 to 2021. The analysis method used is multiple linear regression. The results showed that the independent variable had an effect on the dependent variable as evidenced by the probability value (F-statistic) smaller than α = 5%. The t-test results show that the inflation variable and the open unemployment rate variable affect Economic Growth with a probability value smaller than α = 5%. The coefficient of determination test results show that the dependent variable can be explained by the independent variable by 50.8% and the rest is explained by other variables outside the model.